2018
DOI: 10.1097/inf.0000000000001710
|View full text |Cite
|
Sign up to set email alerts
|

An Observational Study of Severe Pertussis in 100 Infants ≤120 Days of Age

Abstract: These data, as well as data from previous California studies, suggest updated strategies for the management of severe pertussis. These include perform serial white blood cell counts, treat all presumptive cases with azithromycin, evaluate for pulmonary hypertension, intubate and administer oxygen for apneic episodes and administer inotropic/vasoactive agents for cardiogenic shock. Do not administer steroids or nitric oxide. Criteria for exchange blood transfusion therapy for leukocytosis with lymphocytosis are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 31 publications
1
23
0
6
Order By: Relevance
“…A resurgence of pertussis across age groups has occurred in several countries in recent years, specifically in unimmunized (0–8 weeks) or partially immunized (2–6 months) infants [ 43 45 ]. Neonates also have significantly higher rates of complications and death compared with other age groups, which is in line with previous reports [ 44 47 ]. During 1980–2016, in countries such as Australia, Belgium, Brazil, Portugal, the UK and the US where high coverage levels of pertussis vaccination have been reported, a rise in the incidence of pertussis has been observed [ 37 , 46 , 48 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…A resurgence of pertussis across age groups has occurred in several countries in recent years, specifically in unimmunized (0–8 weeks) or partially immunized (2–6 months) infants [ 43 45 ]. Neonates also have significantly higher rates of complications and death compared with other age groups, which is in line with previous reports [ 44 47 ]. During 1980–2016, in countries such as Australia, Belgium, Brazil, Portugal, the UK and the US where high coverage levels of pertussis vaccination have been reported, a rise in the incidence of pertussis has been observed [ 37 , 46 , 48 51 ].…”
Section: Discussionsupporting
confidence: 92%
“…Provisional criteria for ET therapy in patients with leukocytosis (lymphocytosis subtype) have been recently suggested. [ 11 ] As summarized in Table 1 , the survival rate of pertussis patients with hyperleukocytosis is significantly higher when ET therapy is used; however, this therapy has not yet been used in a pertussis patient in China.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that plasma exchange and leukapheresis can reduce leukocyte count and signi cantly improve fatal hypoxemia and pulmonary hypertension [23,24]. Some researchers have used carbon monoxide and sildena l to dilate pulmonary blood vessels and reduce pulmonary hypertension; some e cacy was observed [25].…”
Section: Discussionmentioning
confidence: 99%